2017
DOI: 10.3390/medicines4040071
|View full text |Cite
|
Sign up to set email alerts
|

Qigong Exercise and Arthritis

Abstract: Background: Arthritis is a chronic condition resulting in considerable disability, particularly in later life. Aims: The first aim of this review was to summarize and synthesize the research base concerning the use of Qigong exercises as a possible adjunctive strategy for promoting well-being among adults with arthritis. A second was to provide related intervention directives for health professionals working or who are likely to work with this population in the future. Methods: Material specifically focusing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 72 publications
(115 reference statements)
0
9
0
1
Order By: Relevance
“…Marks [304] reviewed, summarized, and synthesized the research involving the use of qigong exercises in the treatment of arthritis. He concluded that mind-body and relaxation techniques such as those practiced in China for centuries may be a useful intervention strategy for adults having various forms of arthritis.…”
Section: Resultsmentioning
confidence: 99%
“…Marks [304] reviewed, summarized, and synthesized the research involving the use of qigong exercises in the treatment of arthritis. He concluded that mind-body and relaxation techniques such as those practiced in China for centuries may be a useful intervention strategy for adults having various forms of arthritis.…”
Section: Resultsmentioning
confidence: 99%
“…As a type of exercise which plays a positive role in promoting the mind-body interaction, Qigong has been used in the treatment and rehabilitation of various diseases for a long time. Based on statistical methods, the therapeutic effects were proved of Qigong on cancer, cardiovascular disease, chronic pain, hypertension, arthritis and stroke [3,10,36]. Despite the important function of Qigong in promoting health, few studies were conducted to explore the underlying mechanisms with development of scientific technologies to investigate the molecular mechanism of Qigong, mainly focusing on the effect of Qi on various cells [14,17,37].…”
Section: Discussionmentioning
confidence: 99%
“…In modern medical system, Qigong, Yoga, Taichi, and respiratory regulation are different methods of mind-body interaction, which are used in treatment of many human diseases [1]. Qigong, originated in ancient China, is one of the traditional methods for health care, health preservation and disease elimination [1][2][3][4]. Qigong utilizes the modulation of breath, physical activity and consciousness (breath, body and heart) as the means to achieve the purpose of maintaining health [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Benefits are not limited to pain, but cover a wide range of health conditions and include improvements in sleep and fatigue, mental health and respiratory function. Controlled trials and aggregate analyses indicate benefits of qigong for pain [5,13], sleep and fatigue [14], mental health [7,8], respiratory function [15], and multiple other health domains [4]. Several trials which address whether the amount of qigong practice contributes to outcomes within the trial have shown that benefits are related to amount of practice [10,14].…”
Section: Discussionmentioning
confidence: 99%
“…There are many forms of qigong, and heterogeneity of practice forms as well as variations in amounts of practice are challenges for exploring the health benefits of qigong. Nevertheless, there is a growing literature on health benefits of qigong [4], especially for chronic pain, sleep disorders and depression [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%